2018
DOI: 10.1152/ajpcell.00268.2017
|View full text |Cite
|
Sign up to set email alerts
|

Phagocytosis-mediated M1 activation by chitin but not by chitosan

Abstract: Chitin particles have been used to understand host response to chitin-containing pathogens and allergens and are known to induce a wide range of polarized macrophage activations, depending, at least in part, on particle size. Nonphagocytosable particles larger than a macrophage induce tissue repair M2 activation. In contrast, phagocytosable chitin microparticles (CMPs, 1-10 μm diameters) induce M1 macrophages that kill intracellular microbes and damage tissues. However, chitosan (deacetylated) microparticles (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 42 publications
1
27
0
Order By: Relevance
“…Since other PRR (e.g., TLR9 or NOD2) were equally proposed as chitin receptors (e.g., )—but not confirmed by molecular studies or direct binding—our study now for the first time provides conclusive experimental evidence for TLR2 as a primary chitin immune receptor. TLR2 seems to cooperate with TLR1 in agreement with , but possibly an additional receptor contributes to full activation. Our results provide a missing molecular link between fungal infection and the previously observed dependence on TLR2 in murine fungal infection models and, importantly, in patients with the functional rs5743708 (p.753RQ) TLR2 allele .…”
Section: Resultsmentioning
confidence: 87%
“…Since other PRR (e.g., TLR9 or NOD2) were equally proposed as chitin receptors (e.g., )—but not confirmed by molecular studies or direct binding—our study now for the first time provides conclusive experimental evidence for TLR2 as a primary chitin immune receptor. TLR2 seems to cooperate with TLR1 in agreement with , but possibly an additional receptor contributes to full activation. Our results provide a missing molecular link between fungal infection and the previously observed dependence on TLR2 in murine fungal infection models and, importantly, in patients with the functional rs5743708 (p.753RQ) TLR2 allele .…”
Section: Resultsmentioning
confidence: 87%
“…In summary, our overall in silico analysis suggested that CD68 and its chitin‐related co‐expression signature may be particularly involved in in vivo M1/M2 macrophage polarization in chitin‐like responses that may control the extent of inflammatory cell recruitment and post‐inflammatory remodeling of peri‐implant tissues and thereby may predetermine the likelihood of subsequent aseptic loosening.…”
Section: Resultsmentioning
confidence: 92%
“…Chitin oligomers released by endochitinases induce the host defense‐related activation of polarized macrophages, which is dependent on the particle size and shape . Non‐phagocytosable (larger than a macrophage) chitin particles may induce M2 activation aimed at tissue repair.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations